Root and tuber crops in St. Kitts - Crossman, S.M.A. (International Center for Tropical Agriculture, 1986)
The offer, availability, and characteristics of cultivated land, cropping systems, yields, the socioeconomic profile of farmers, production vol. and costs, and the marketing of root and tuber crops grown in St. Kitts (sweet potato, yam, cocoyam, taro, and potato) are briefly analyzed. Government policies on root crop production are reviewed. There is only limited production of cassava starch and CM. (CIAT)